A High-Level API for Dynamic Load Balancing in Large-Scale Parameter Sweeps - Salzmann, Philip; Thoman, Peter; Fahringer, Thomas (International journal of parallel programming, 2025)
Parameter sweep studies, such as virtual drug screening, may exhibit significant load imbalance during batched execution on large-scale clusters, resulting in idle and thus wasted resources. Work stealing is a popular method for dynamic load balancing in such scenarios. However, we demonstrate that work stealing alone falls short in cases where a few ranks generate long running high-cost jobs, particularly towards the end of a computation. To address this challenge, we propose high-cost probing, a mechanism for distributing high-cost jobs across workers early during program execution by leveraging user-provided cost hints. We extend the Celerity programming model for distributed accelerator computing with a high-level API tailored to expressing parameter sweep-style workflows that may benefit from high-cost probing. We demonstrate the effectiveness of our approach on synthetic benchmarks as well as a real-world virtual screening application with a highly irregular workload, achieving a 73 percentage point reduction in load imbalance on 128 GPUs.